The effects of the war on the Ukraine economy: The situation at the end of 2022 - Lauri Heinonen; Iikka Korhonen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This brief presents an overview of Ukraine's economy before and during the first ten months of the Russo-Ukraine war, as well as some preliminary considerations for the post-war economy. Although Ukraine's economic growth trailed many of its peers in the years leading up the invasion, the country possesses certain economic and institutional strengths over most countries at a similar level of development. While these strengths should make reconstruction less difficult, the situation remains fraught with difficulties. Many of the activities that make the largest economic contributions, particularly to exports, take place in the eastern regions of Ukraine or in the Kyiv capital region. These areas have either been temporarily occupied by Russia or face a greater military threat by Russia than the poorer, more peaceful, western parts of the country. The country's public finances are deeply in deficit, so restoring strong export revenues is critical to Ukraine's economic recovery. As long as the war continues, Ukraine's public finances and military efforts must largely be financed by foreign partners.
urn:nbn:fi-fe202301204994
Keywords: 330; Ukraine; recovery; war; Russia